Alkali-Active Sand Slate Powder for Use as Mineral Admixture in Mass Hydraulic Concrete: Technical and Economic Analysis. (29th November 2021) - Chen, Xia; Zhou, Xian; Peng, Ziling; Li, Jiazheng
Abstract : This work has launched a comprehensive investigation on the macro performance and micro structure of mass concrete produced with alkali-active sand slate powder (ASSP) for use as the mineral admixture and a thorough analysis on its technical and economic effects is also conducted. Results indicated ternary blend with hybrid of 5–8 wt.% silica fume (SF) and 15–20 wt.% ASSP has the optimal compressive and flexural strength. ASSP particle participates in hydration, accelerates hydration of cement clinker within 8.5 hours, and reduces the autogenous strain of pastes by 164 × 10 −6 in case of dosage less than 25% by mass. Improvement in the mechanical and deformation properties of concrete produced with the hybrid of SF and ASSP is attributed to better particles gradation, compactness enhancement, and transformation in products of hydration. On the whole, it provides another new approach for use of alkali-active rock after second processing as mineral admixture in hydraulic concrete in terms of good performance and economic effects.